Students' Perception Towards the Use of Pictured Story Books to Improve Reading Interest in SDK Majamere - Florensia C. Tuga, Antonia; Yuliana Kua, Maria (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2024)
Someone who loves to read has a strong urge to read to learn new things and gain new perspectives. Based on observations made, it was found that the reading interest of students at SDK Majamere is still low. There are students who have difficulty reading, and there are also those who are completely unable to do so. The purpose of this study was to determine whether the use of picture books can increase the enthusiasm for reading of students at SDK Majamere. This type of research is descriptive qualitative. Data collection techniques used are observation, interviews, documentation and questionnaires. The instrument used is a student response questionnaire. The subjects in this study were grade III students with a total of 12 students. Based on the questionnaire statement, it can be concluded that the results of the student response questionnaire regarding the use of picture story books to increase reading interest are in the agree category with an average of 71%. The use of picture story books can influence students' reading interest and level of understanding, encourage activeness and curiosity, help students' imagination in understanding the contents of the reading so that they more often associate what they read with what they experience and are able to create their own stories in short language.